Effect of salmeterol on respiratory muscle activity during exercise in poorly reversible COPD. Issue 6 (28th May 2004) - Man, W D C; Mustfa, N; Nikoletou, D; Kaul, S; Hart, N; Rafferty, G F; Donaldson, N; Polkey, M I; Moxham, J
Abstract : Background: Some patients with irreversible chronic obstructive pulmonary disease (COPD) experience subjective benefit from long acting bronchodilators without change in forced expiratory volume in 1 second (FEV1 ). Dynamic hyperinflation is an important determinant of exercise induced dyspnoea in COPD. We hypothesised that long acting bronchodilators improve symptoms by reducing dynamic hyperinflation and work of breathing, as measured by respiratory muscle pressure-time products. Methods: Sixteen patients with "irreversible" COPD (<10% improvement in FEV1 following a bronchodilator challenge; mean FEV1 31.1% predicted) were recruited into a randomised, double blind, placebo controlled, crossover study of salmeterol (50 μg twice a day). Treatment periods were of 2 weeks duration with a 2 week washout period. Primary outcome measures were end exercise isotime transdiaphragmatic pressure-time product and dynamic hyperinflation as measured by inspiratory capacity. Results: Salmeterol significantly reduced the transdiaphragmatic pressure-time product (294.5 v 348.6 cm H2 O/s/min; p = 0.03), dynamic hyperinflation (0.22 v 0.33 litres; p = 0.002), and Borg scores during endurance treadmill walk (3.78 v 4.62; p = 0.02). There was no significant change in exercise endurance time. Improvements in isotime Borg score were significantly correlated to changes in tidal volume/oesophageal pressure swings, end expiratory lung volume, and inspiratory capacity, but not pressure-time products. Conclusions: Despite apparent "non-reversibility" in spirometric parameters, long acting bronchodilators can cause both symptomatic and physiological improvement during exercise in severe COPD.